Caviar versus brill eggs: A novel high performance liquid chromatography‐mass spectrometry application for evaluating cosmetic ingredients composition. Issue 2 (19th May 2016) - Dal Bello, Federica; Santoro, Valentina; Aigotti, Riccardo; Medana, Claudio; Gastaldi, Daniela; Baiocchi, Claudio
Abstract : In this study, raw materials, sturgeon and brill roe, were analyzed and compared as regard their use in cosmetic products. Recently, expensive caviar was largely used in beauty creams as lipids source. We compared lipids from caviar and brill eggs to propose a technological alternative. The fatty acids amount was determined with a new GC‐MS method. The triacylglycerols were identified and characterized by HPLC coupled with high resolution MS (HRMS). Both techniques showed a higher content of fatty acids and triacylglycerols in caviar respect to brill eggs. Some fatty acids, such as linoleic and linolenic acids, which are recognized to enhance skin metabolism, are absent, or show very low concentration, in brill eggs respect to sturgeon ones. It was possible to conclude that brill eggs are not a proper substitute of caviar in the formulation of cosmetic. Practical application: The developed analytical techniques provided a satisfactory analytical characterization of the raw materials. Although the sample preparation for GC‐MS analysis is quite time consuming due to the derivatization of fatty acids, the one for triacylglycerols analyzed by HPLC‐HRMS is very fast, and involves the use of a small amount of organic solvent. Fatty acids and triacylglycerols were identified and characterized. Comparison between Acipenser trasmontanus (caviar) and Scophthalmus rhombus eggs as active ingredient in beauty cream. A fatty acid quantitation and triacylglycerols quantitation, and characterization methods are showed. GC‐MS and HPLC‐HRMS are satisfactory tool to provide a full description of the studied raw materials. Abstract : Comparison between Acipenser trasmontanus (caviar) and Scophthalmus rhombus eggs as active ingredient in beauty cream. A fatty acid quantitation and triacylglycerols quantitation, and characterization methods are showed. GC‐MS and HPLC‐HRMS are satisfactory tool to provide a full description of the studied raw materials.